The Effect of Percentage Variation of Ketapang Fruit Biobrickets on Health Value and Combustion Rate - Fadilah, Himmi Raudatul; Ahzan, Sukainil; Pangga, Dwi; Habibi, Habibi; Bilad, Muhammad Roil (Indonesian Review of Physics, 2023)
This study aims to determine the effect of variations in the percentage of Ketapang fruit (KF) bio briquette on calorific value and burning rate. This research is experimental in a physics laboratory with a literature review carried out in three stages, namely the preparation stage, the bio briquette manufacturing stage, and the bio briquette testing stage. The main ingredient used in the manufacture of bio briquettes is Ketapang fruit. The adhesive materials used were tapioca flour and sago flour with percentages of 10%, 12.5% ​​and 15%. The results showed that the calorific value of the following bio briquettes using the tapioca predicate included 5,139.45 Cal, 5,540.97 Cal, 5,922.42 Cal, and those using the sago predicate including 2,409.12 Cal, 3,653.83 Cal, 3,894.74 cal. The highest calorific value was in bio briquettes with tapioca adhesive type in the sample at 85%:15%. The burning rate of bio briquettes using tapioca glue included 1.98 gr/minute, 1.76 gr/minute, 1.62 gr/minute and those using sago glue included 2.62 gr/minute, 2.50 gr/minute, 2.31 gr/minute. The lowest burning rate value was in bio briquettes with the type of sago glue in the sample at 85%:15%. Based on the test results, it is known that the lower the percentage of keta pang fruit in the bio briquettes, the lower the burning rate, and the resulting calorific value increases.